2008
DOI: 10.1016/j.jvs.2008.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia and fibromuscular dysplasia of infrarenal abdominal aorta with downstream aneurysm: Case report and review of the literature

Abstract: Fibromuscular dysplasia represents one of the more common types of arterial fibrodysplasia, a heterogeneous group of nonatherosclerotic vascular occlusive and aneurysmal diseases. This disorder mainly affects renal and cerebral arteries, and less frequently, arm, leg, and visceral arteries. Exceptionally, it has been described in the abdominal aorta. Aortic hypoplasia is a tubular narrowing of a long segment of the aorta and is a rare congenital defect, different from coarctation, which is a focal stricture. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Odero et al reported a 77-year-old man with infrarenal aortic FMD and monoclonal gammopathy. 8) To the best of our knowledge, this is the first case report of FMD and hypereosinophilia. The association between the pathogenesis of these diseases is unclear, although the genetic abnormality may be assumed to be one of the important factors between these diseases.…”
Section: Discussionmentioning
confidence: 78%
“…Odero et al reported a 77-year-old man with infrarenal aortic FMD and monoclonal gammopathy. 8) To the best of our knowledge, this is the first case report of FMD and hypereosinophilia. The association between the pathogenesis of these diseases is unclear, although the genetic abnormality may be assumed to be one of the important factors between these diseases.…”
Section: Discussionmentioning
confidence: 78%
“…A few histologically confirmed cases are reported from intracranial vessels, but Kimura et al (6) only confirmed the medial hyperplasia type of FMD associated with aneurysm of the VA and posterior inferior cerebellar artery. Both hypoplasia and FMD in same vessel was only reported from abdominal aorta (7), but there was medial hyperplasia type of FMD associated with aneurysm. This is the first report consists of hypoplasia and intimal type FMD of the VA.…”
Section: Discussionmentioning
confidence: 92%
“…Most common presentations are renovascular hypertension and stroke. Fibro muscular dysplasia as a cause of abdominal aortic aneurysm is rather rarely reported [2,3,4]. Here we report a case of fibro muscular dysplasia associated with abdominal aortic aneurysm who presented with vague abdominal discomfort and claudication pain of both lower limbs.…”
Section: Introductionmentioning
confidence: 82%
“…Most common presentations are renovascular hypertension and stroke. Fibro muscular dysplasia as a cause of abdominal aortic aneurysm is rather rarely reported [2,3,4]. Clinical presentations of patients with FMD are varied.…”
Section: Discussionmentioning
confidence: 99%